2017
DOI: 10.1080/07373937.2017.1402022
|View full text |Cite
|
Sign up to set email alerts
|

Fast drying of cut tobacco in drop tube reactor and its effect on petroleum ether tobacco extracts

Abstract: Entrained flow drying is an important fast drying tool in tobacco industry. This study used a drop tube reactor (DTR) as an entrained flow dryer to investigate drying process of flue-cured cut tobacco. Lab-scale cold and hot DTRs were set up to obtain drying kinetics for three types of cut tobacco using different drying gases and temperatures. The effective diffusion coefficients of cut tobacco in DTRs were compared with those in a general cylinder dryer. Moreover, the effects of different drying gases and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Te temperature and moisture evolution of cut tobacco at diferent air temperature combinations were in good agreement with simulation results by the model [8]. Li et al reported that the drying temperature increase can result in decrease of the petroleum ether tobacco extract [9]. In Wang et al's research on the infuence of tobacco drying on the subsequent pyrolysis and combustion characteristics, the results showed that low-temperature drying (at 70 and 110 °C) had little efect on the pyrolysis and combustion properties, but high-temperature drying (at 150 and 170 °C) led to a considerable reduction of sugar while producing new components that are harder to decompose [10].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Te temperature and moisture evolution of cut tobacco at diferent air temperature combinations were in good agreement with simulation results by the model [8]. Li et al reported that the drying temperature increase can result in decrease of the petroleum ether tobacco extract [9]. In Wang et al's research on the infuence of tobacco drying on the subsequent pyrolysis and combustion characteristics, the results showed that low-temperature drying (at 70 and 110 °C) had little efect on the pyrolysis and combustion properties, but high-temperature drying (at 150 and 170 °C) led to a considerable reduction of sugar while producing new components that are harder to decompose [10].…”
Section: Introductionsupporting
confidence: 83%
“…Tere are many studies reported on the physical and chemical changes during the tobacco drying process [7][8][9][10][11][12]. Zhu has studied the two-stage drying of cut tobacco [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Drying as a process of removing moisture has been widely used in different kinds of biomass treatments, such as with biofuels (1), fruits and vegetables (2), milk (3)(4), tea (5) and tobacco (6). Distinct dryers were developed and applied for biomass-drying based on a variety of treatment purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible fibrous particles are a special type of particles that have extensive applications in the industries, including energy, food, chemical, and environmental fields . In particular, these particles, like biomass fuels, tea leaves, and tobacco stems, are easily bundled and aggregated together due to their structural characteristics of nonuniform shape. Unlike other types of particles, the flexible fibrous particles can be easily associated with higher-order structures with little quantitative changes and formed as clusters. However, these clusters are generally hard to be disappeared during the industrial process. These relevant processes like transportation and drying are found to be strongly dependent on their structural properties.…”
Section: Introductionmentioning
confidence: 99%